2022
DOI: 10.1002/cmdc.202200040
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Gold Catalyst for the Oxidative N‐Dealkylation of Drug Molecules: A Method for Synthesis of N‐Dealkylated Metabolites

Abstract: A novel method for the selective catalytic N‐dealkylation of drug molecules on a nanoporous gold (NPG) catalyst producing valuable N‐dealkylated metabolites and intermediates is described. Drug metabolites are important chemical entities at every stage of drug discovery and development, from exploratory discovery to clinical development, providing the safety profiles and the ADME (adsorption, distribution, metabolism, and elimination) of new drug candidates. Synthesis was carried out in aqueous solution at 80 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…A more unusual oxidation reaction that is one of the very few applied reactions is the oxidative dealkylation or cyclization of lidocaine, which was performed to synthesize a drug metabolite (Scheme E) . This reaction can yield two products, depending entirely on the reaction conditions, but in a selective fashion.…”
Section: Catalysis By Nanoporous Gold In Organic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…A more unusual oxidation reaction that is one of the very few applied reactions is the oxidative dealkylation or cyclization of lidocaine, which was performed to synthesize a drug metabolite (Scheme E) . This reaction can yield two products, depending entirely on the reaction conditions, but in a selective fashion.…”
Section: Catalysis By Nanoporous Gold In Organic Synthesismentioning
confidence: 99%
“…618 A more unusual oxidation reaction that is one of the very few applied reactions is the oxidative dealkylation or cyclization of lidocaine, which was performed to synthesize a drug metabolite (Scheme 2E). 619 This reaction can yield two products, depending entirely on the reaction conditions, but in a selective fashion. It needs pointing out that this is one of the very few reactions, in which a peralcohol, tert-butylperoxide, can also be used as the oxidant, which may be more easily administered than O 2 in a synthetic organic chemistry laboratory.…”
Section: Oxidation Reactions Of Organic Molecules By Nanoporous Goldmentioning
confidence: 99%
“…The plots illustrate the absence of lidocaine (1) (m/z 235) in the breakthrough fraction, which is dominated by the deethylated product norlidocaine (2) (m/z 207). This fraction also contains a byproduct at m/z 233, which was identified as a cyclized form of lidocaine (4) [12]. Increasing the percentage of organic solvents like methanol or acetonitrile in water led to reduced conversion, with no conversion at all in the absence of water.…”
Section: Plug-flow Optimizationmentioning
confidence: 99%
“…Application of larger diameter particles to more complex substrate molecules in the liquid phase is less common. We have previously shown that certain drugs can be dealkylated in the liquid phase using nanoporous gold in a batch cell set-up [12]. Dealkylation is one of a number of Phase-I metabolic oxidation reactions catalyzed by members of the Cytochrome P450 enzyme family.…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoints of green and sustainable chemistry, the use of O 2 as the terminal oxidants for the oxidative cleavage of C–N bonds in N , N -dialkylamines or N -alkylamines represents an environmentally friendly and economical methodology . The oxidative cleavage of C–N bonds in N , N -dialkylamines into N -alkylamines has been well documented over noble or non-noble metal catalysts. , However, the further oxidative cleavage of C–N bonds in N -alkylamines into primary amines remains a challenging target, and it has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%